Decision Making Problem for Medical Diagnosis Using Hexagonal Fuzzy Number Matrix - Sandhiy, S; Selvakumari, K (International Journal of Engineering and Technology, 2018)
Fuzzy set theory plays a vital role in medical fields. There are varieties of models involving fuzzy matrices to deal with different complicated aspects of medical diagnosis. Fuzzy set theory is highly suitable and applicable for developing knowledge based system in medicine for the tasks of medical findings. The field of medicine and decision making are the most fruitful andinteresting area of applications of fuzzy set theory. In this paper, we have applied the notion of Hexagonal fuzzy membership matrix in a medical diagnostic model. The advantage of this model is, if the patient-matrices are known, then it is possible to find which patient is suffering from what kind of disease. Most probably the fuzzy decision model in which overall ranking or ordering of different fuzzy sets are determined by using comparison matrix.Â Â Â